Therapeutic Companions: characterization of professional practice in the perspective of Behavior Analysis (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
Therapeutic Accompaniment as a clinical practice was born in the antipsychiatry political-ideological movement. Most research papers try to build a Therapeutic Accompaniment profile from the beginning of this historical context, but the concept has not yet reached a scientific consensus. Although there are some common characteristics, the Therapeutic Accompaniment’s diverse practice makes it difficult to identify the variables and consequently to built a final concept. The main purpose of this study was to characterize therapeutic companions under the behavior analysis perspective. Thirteen Therapeutic Companions, of both sexes, participated of this research. They were from the city of São Paulo and submitted to a semi-structured interview. The results were analyzed in four analysis dimensions and unfolded in categories. It is possible to observe that the Therapeutic Accompaniment’s profiles are constantly changing and to characterize them imply the observation of many variables that will be discussed here.
Keywords: therapeutic companions; behavior analysis; clinical psychology